2020
DOI: 10.1038/s41467-020-17277-3
|View full text |Cite
|
Sign up to set email alerts
|

“Gene accordions” cause genotypic and phenotypic heterogeneity in clonal populations of Staphylococcus aureus

Abstract: Gene tandem amplifications are thought to drive bacterial evolution, but they are transient in the absence of selection, making their investigation challenging. Here, we analyze genomic sequences of Staphylococcus aureus USA300 isolates from the same geographical area to identify variations in gene copy number, which we confirm by long-read sequencing. We find several hotspots of variation, including the csa1 cluster encoding lipoproteins known to be immunogenic. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…These genes are not always conserved together (Liu et al, 2015), and their presence has been associated with bone infection (Sabat et al, 2006), resistance to host immunity (Sitkiewicz, Babiak & Hryniewicz, 2011;Askarian et al, 2017), biofilm formation (Barbu et al, 2014), and host-cell adhesion (Corrigan, Miajlovic & Foster, 2009;Cheng et al, 2009;Barbu et al, 2010;Askarian et al, 2016). Belikova et al (2020) showed that in USA300 sdr genes undergo frequent within-genome recombination during growth in lab conditions and during infection. The high number of synonymous mutations may be the result of repeats expanding or collapsing in evolved strains, causing base-calling artefacts when mapped onto the reference genomes.…”
Section: Patterns Of Acquisition Of Snps At Visa Endpoints Is Influenced By Genetic Backgroundmentioning
confidence: 99%
“…These genes are not always conserved together (Liu et al, 2015), and their presence has been associated with bone infection (Sabat et al, 2006), resistance to host immunity (Sitkiewicz, Babiak & Hryniewicz, 2011;Askarian et al, 2017), biofilm formation (Barbu et al, 2014), and host-cell adhesion (Corrigan, Miajlovic & Foster, 2009;Cheng et al, 2009;Barbu et al, 2010;Askarian et al, 2016). Belikova et al (2020) showed that in USA300 sdr genes undergo frequent within-genome recombination during growth in lab conditions and during infection. The high number of synonymous mutations may be the result of repeats expanding or collapsing in evolved strains, causing base-calling artefacts when mapped onto the reference genomes.…”
Section: Patterns Of Acquisition Of Snps At Visa Endpoints Is Influenced By Genetic Backgroundmentioning
confidence: 99%
“…In other cases, phenotypic heterogeneity arises without the involvement of environmental cues, and the underlying mechanisms are diverse. Genetic mechanisms include site-specific recombination (Scott and Simon, 1982;Reyes Ruiz et al, 2020), slipped-strand mispairing at tracts of repetitive DNA sequences (Moxon et al, 2006), and amplification of specific genome regions (Belikova et al, 2020;Tomanek et al, 2020). As described below, cell diversification into two or more phenotypic states can also be driven by nongenetic mechanisms, such as propagation of feedback loops (Ferrell, 2002) and formation of DNA methylation patterns .…”
Section: Introductionmentioning
confidence: 99%
“…Belikova et al. ( 79 ) observed that gene duplication and amplification occur frequently in the Staphylococcus aureus chromosome, concentrated in loci containing repetitive DNA elements that facilitate recombination; findings were consistent with an “accordion” model with high copy-number variants favored under selective conditions. An especially affected locus encoding “conserved staphylococcal antigens 1” ( csa1 ) displayed amplification up to 10 copies in clinical isolates, while introduction of an antibiotic resistance cassette within the locus resulted in amplifications up to 100- to 200-fold in the setting of antibiotic pressure ( 79 ).…”
Section: Discussionmentioning
confidence: 75%